Canadian Highly Sensitized Patient Program Report: A 1000 Kidney Transplants Story - M. Khaled Shamseddin; Steven Paraskevas; Rahul Mainra; Kyle Maru; Bailey Piggott; Darlene Jagusic; Kathy Yetzer; Lakshman Gunaratnam; Christine Ribic; Joseph Kim; Sunita Singh; Stephanie Hoar; et al. (Canadian Journal of Kidney Health and Disease)
Purpose: Highly sensitized patients (HSPs) with kidney failure have limited access to kidney transplantation and poorer post-transplant outcomes. Prioritizing HSPs in kidney allocation systems and expanding the pool of deceased donors available to them has helped to reduce their wait times for transplant and enhanced post-transplant outcomes. The Canadian HSP Program was established by Canadian Blood Services in collaboration with provincial organ donation and transplantation programs throughout the country to increase transplant opportunities for transplant candidates needing very specific matches from deceased kidney donors. Highly sensitized patients in the Canadian Program are defined by a calculated panel-reactive antibody (cPRA) ≥95%. In this report, we describe the evolution and trajectory of the Canadian HSP Program and evaluate the national impact on the first 1000 kidney transplant cases. Source of Information: To allocate deceased donor kidney organs nationally to HSPs and report on the Canadian HSP Program’s performance, Canadian Blood Services developed a national database registry known as the Canadian Transplant Registry (CTR) and an online reporting tool known as the Canadian HSP Program Data Dashboard. Methods: The CTR, which collects HSPs’ data for the purpose of matching potential donors to HSPs and as part of required national quality, safety, and efficiency performance measurements, was retrospectively reviewed. Due to the nature of using deidentified aggregate registry data, a patient consent form was not required. A Research Ethical Board (REB) application was also waived. Key Findings: In this article, we describe the historical development, initial deployment, and evolution of the Canadian HSP Program with a primary aim to increase the rate of deceased donor kidney transplantation. A secondary aim was to evaluate the national impact of the Canadian HSP Program on the first 1000 kidney transplant cases. Transplant candidates who have participated in the Canadian HSP Program and recipients who received transplants were predominantly females (average age 50 years, female 62%) with blood group O (47% of candidates, 42% of transplants). Seventy percent of all active transplant candidates enrolled in the HSP Program were in the hardest to match group (cPRA ≥99%), and only 22% of the transplant candidates with cPRA of 100% have received a transplant to date through the Program. The average times from first participation in the Canadian HSP Program to transplantation for cPRA ≥99% transplant recipients were significantly longer than for cPRA 95% to 98% recipients averaging 22 months versus 6 months, respectively. By the end of June 2024, the Canadian HSP Program had facilitated 1000 transplants, 613 of which were from interprovincial matches. The average (SD) cold ischemic time (CIT) was 14.5 (5.9) hours, with interprovincial transplants exhibiting significantly longer CITs compared with intraprovincial transplants, averaging an additional 4.7 hours. Limitations: Our study limitations include first that it is a retrospective registry data analysis with no available short- and long-term clinical outcomes data at this point (patient and graft survival). Second, given the nature of registry data, not all relevant data may have been captured and reporting may not be complete for all patients. Implications: Examination of CTR registry data showed the Canadian HSP Program had a meaningful impact in enabling 1000 HSPs to access transplantation opportunities that may otherwise be unavailable to them.